2013
DOI: 10.1016/j.psychres.2013.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment cortisol levels predict posttreatment outcomes among older adults with depression in cognitive behavioral therapy

Abstract: Previous studies suggest that individuals with elevated levels of cortisol (the “stress hormone”) could be particularly resistant to treatment for depression. However, most of these studies have been conducted in the context of antidepressant medications, and no study has examined pretreatment cortisol levels as a predictor of treatment outcomes among older adults with depression in cognitive-behavioral therapy (CBT), despite the relevance of this population for such a research question. The current study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 88 publications
(94 reference statements)
0
20
1
Order By: Relevance
“…The studies employing such measures found higher rather than lower cortisol concentrations predicted non‐responses to psychological therapy . This appears to stand in contrast to the findings of the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The studies employing such measures found higher rather than lower cortisol concentrations predicted non‐responses to psychological therapy . This appears to stand in contrast to the findings of the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…One explanation for this discrepancy is that postchallenge values require repeated sampling schedules and as such provide more reliable estimates of pretreatment HPA axis functioning than single time point measures, which are often used for resting cortisol. Indeed, only studies using cumulative measures of resting cortisol, such as 24‐h urine samples or repeated saliva sampling over the course of at least one day , seem to be able to demonstrate a link with treatment outcomes. By contrast, studies using one‐off morning blood samples or saliva samples immediately before a therapy session were unable to yield positive findings, which may have also been also due to anticipatory stress linked with venipuncture or treatment.…”
Section: Introductionmentioning
confidence: 99%
“…20 In total, eight studies were eligible for data extraction. [17][18][19][20][21][22][23][24] Tables DS1 shows the characteristics of these studies.…”
Section: Search Resultsmentioning
confidence: 99%
“…Two studies focused on adolescents 17,21 and one looked at older adults. 22 The majority of patients had a major depressive disorder according to the DSM, and in most instances, patients had moderate to severe depression. Patients with major comorbid mental disorders, including substance use, psychotic and bipolar disorders, were mostly excluded.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
“…It is possible that hyperarousal is a common predictor of a range of clinical interventions given that recently our group noted some evidence of elevations in TSST in depressed adolescents who show more favorable responses to psychopharmacological treatment [ 18 ]. However, a deeper understanding of stress system functioning across development is needed as this pattern does not typically hold for depressed adults undergoing psychosocial or psychopharmacological treatment [ 19 ]. There are some aspects of stress system functioning that do not seem to be associated with intervention outcomes including indices of self-reported experienced stress, experimenter-rated expressed stress, and basal cortisol for these participants that was collected at the end of the school day [ 20 ].…”
Section: Discussionmentioning
confidence: 99%